A graded cluster system to mine virtual stations in free-floating bike-sharing system on multi-scale geographic view. (25th January 2021) - Liu, Yixiao; Tian, Lixin
Abstract: Bike sharing is one of the means of green travel. On the one hand, sharing bicycles facilitates people's travel and enriches the way of travel. On the other hand, sharing bicycles improves people's awareness and sense of responsibility for energy saving and emission reduction, which in turn reflects the meaning of green travel. In order to support people using shared bicycles for green travel, it is very important to optimize the configuration of bike-sharing system. The increasing amounts of free-floating bicycles give a serious challenge in parking planning. Dispatching random parking bicycles will increase vehicles workload and offset emission reduction effect of the bicycles. At this paper we discuss about the virtual stations in a free-floating bike-sharing system. Virtual stations are the focus of efficient and environmentally friendly dispatching, which enable the bike-sharing company to achieve cleaner production. We introduce the modifiable areal unit problem and propose a new method called the graded cluster system to mine virtual stations on a multiscale geographic view. The new method can generate more virtual stations more evenly. This not only makes it more convenient for people to use shared bicycles for green travel, but also dense virtual stations can make shared bicycles more visible in people's sight, strengthening people's awareness of green travel.